LINGUOCULTURAL FEATURES OF TRANSLATIONS OF TOPONYMS IN “BABURNOMA” (International journal of artificial intelligence, 2024)
The memoirs of Zakhiriddin Muhammad Babur are a unique text not only within the literature written in a Turkic language. It is a long prose text most probably written in a cultivated but at the same time colloquial language. The text deals with many types of information and sometimes reveals even the emotions of the author. The author himself is bilingual in Chagatai Turkic and Persian and educated in the Islamic sense of his time and his homeland. Thus, the text is a premium source to learn many things about the Chagatai language of this period. Another aspect of the poetic originality in the Boburnoma is that geographical location, terms, names, and personal names are expressed through pictorial means, as well as in popular expressions.